Outcome of Carpal Tunnel Release: a prospective study - Pradhan, NMS; Khan, JA; Acharya, BM; Devkota, P; Rajbhandari, A (Nepal Orthopaedic Association Journal, 2013)
BACKGROUND: Carpal tunnel syndrome (CTS) is the most common peripheral entrapment neuropathy and is manifested by characteristic signs and symptoms resulting from median nerve compression at the carpal tunnel. The diagnosis is essentially clinical, which is further confirmed by nerve conduction studies. Surgical release of the transverse carpal ligament is advised when conservative treatment fails. METHODS: This prospective study evaluates the outcome of standard open carpal tunnel release performed at our center* from June 2004 to July 2007. Thirty two patients with idiopathic carpal tunnel syndrome, with failed conservative treatments, either with NSAIDs and/or local infiltration with corticosteroid injections plus night splint, or recurrence after conservative treatment were subjected to open carpal tunnel release after getting approval from the local ethical committee and getting a written and informed consent from the patient. Clinical assessment was done preoperatively and at 6 weeks, 3 months and 6 months following the procedure and included the two-point discrimination test at the tip of the index finger and Boston questionnaires as an outcome measurement of symptoms severity. All the patients were followed up for a period of six months. RESULTS: All the patients presented improvement in the postoperative evaluations in all the analyzed parameters. CONCLUSION: Open carpal tunnel release is a safe and effective method for the treatment of CTS and can be carried out when the conservative means fail to relieve the symptoms. DOI: http://dx.doi.org/10.3126/noaj.v1i1.8129 Nepal Orthopaedic Association Journal Vol.1(1) 2010